PEMODELAN DAN PENGENDALIAN MOTOR DC MENGGUNAKAN SIMULASI MATLAB - Arifin, Yusnaini; Amir, Ardi (MEKTEK, 2010)
This study aimed to see how the response changes in the speed DC motor and the armature current at the time of starting and stopping. The method used is a simulation using matlab software. By using the data specification n =Ï‰Dripproof type DC motors as well as testing the obtained value of Ï‰n =55.44 rad / sec and Î¾ =0.3518. Because value Î¾ smaller than one, then the DC motor has a characteristic of less damped (underdamped).